Composite sodium ion battery solid electrolyte and preparation method thereof

By using composite electrolytes of high-performance polymers and dispersed modified carbon nanotubes in sodium ion batteries, the low conductivity and stability of solid electrolytes are solved, significantly improving the performance and safety of the battery, suitable for commercial use .

CN119253030APending Publication Date: 2025-01-03JIANGSU CHUANYI NADIAN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364543.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing solid electrolytes of sodium ion batteries have problems such as low ion conductivity, poor interfacial compatibility and poor chemical stability, which limits the development of sodium ion batteries.

Method used

Using a solid electrolyte of composite sodium ion battery, including high-performance polymers, dispersed modified carbon nanotubes, sodium perchlorate and azobisisobutyronitrile, mixed by stirring and drying and cutting into molding in a vacuum drying box , an electrolyte with high ionic conductivity and excellent chemical stability was prepared.

Benefits of technology

It effectively improves the ionic conductivity of solid electrolytes, improves electrochemical performance and cycle stability, extends service life, and avoids the safety hazards of liquid electrolytes, and is suitable for large-scale commercial applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, in particular to a composite sodium ion battery solid electrolyte and a preparation method thereof, which are used for solving the problems of low ionic conductivity, poor interfacial compatibility and poor chemical stability of the existing solid electrolyte. According to the preparation method, the high-performance polymer is used as a main raw material, the dispersed and modified carbon nanotubes are added into the high-performance polymer, the advantages of all the components are fully played, the ionic conductivity of the solid electrolyte is effectively improved, the electrochemical performance of the sodium-ion battery is effectively improved, and the sodium-ion battery has excellent chemical stability; compared with the prior art, the all-solid-state sodium-ion battery has the advantages that the cycle stability and safety of the all-solid-state sodium-ion battery are remarkably improved, the service life is prolonged, the potential safety hazards of volatile, explosion and the like of the traditional liquid electrolyte are avoided, and the preparation method is simple, feasible, easy to operate, low in cost and beneficial to large-scale commercial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a composite sodium ion battery solid electrolyte and a preparation method thereof. Background Art

[0002] With the rapid development of renewable energy, the demand for large-scale energy storage systems is increasing. As a potential alternative to lithium-ion batteries, sodium-ion batteries have attracted much attention due to their abundant resources and low cost. However, most traditional sodium-ion battery electrolytes use liquid organic electrolytes, but this electrolyte has safety risks, such as combustion and leakage, which limits its commercialization progress.

[0003] In recent years, solid electrolytes have received extensive attention in the field of sodium-ion batteries. Solid electrolytes have become one of the hot topics in sodium-ion battery research due to their high safety and good mechanical properties. However, existing solid electrolytes still have problems such as low ionic conductivity, poor interfacial compatibility, and poor chemical stability, which limit the further development of sodium-ion batteries. Therefore, it is of great significance to develop a composite sodium-ion battery solid electrolyte and its preparation method. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a composite sodium ion battery solid electrolyte and a preparation method thereof, which solves the problems of low ionic conductivity, poor interface compatibility and poor chemical stability of existing solid electrolytes.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A composite sodium ion battery solid electrolyte comprises the following components in parts by weight:

[0007] 32-36 parts of high-performance polymer, 0.5-2.5 parts of dispersed modified carbon nanotubes, 8-10 parts of sodium perchlorate, 0.01-0.03 parts of azobisisobutyronitrile and 75-85 parts of anhydrous tetrahydrofuran;

[0008] Wherein, the high performance polymer is prepared by the following steps:

[0009] Step a1: 5-bromo-1-pentanol, 1-methylpyrrolidine, anhydrous potassium carbonate and anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 0-5°C and a stirring rate of 300-400 r / min for 1-2 hours, and then the mixture is heated to 50-55°C and stirred for reaction for 8-10 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at a temperature of 50-55°C for 3-5 hours to obtain a cationic intermediate;

[0010] Step a2: Add the cationic intermediate, triethylamine and anhydrous acetonitrile to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 0-5°C and a stirring rate of 300-400r / min, then add methacryloyl chloride solution dropwise while stirring, and control the dropping rate to 1-2 drops / s. After the dropwise addition is completed, continue to stir and react for 20-30 minutes, then continue to stir and react for 4-5 hours under the condition of heating to 45-50°C. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, and then wash with petroleum ether 2-3 times to obtain a cationic monomer;

[0011] Step a3: Add vinyl ethylene carbonate, trifluoroethyl methacrylate, cationic monomer, azobisisobutyronitrile and deionized water into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction at a temperature of 20-25°C and a stirring rate of 300-400r / min for 1-2h, then raise the temperature to 65-75°C and continue stirring the reaction for 8-10h. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent, and then place it in a vacuum drying oven and dry it at a temperature of 50-55°C for 5-6h to obtain a high-performance polymer.

[0012] As a further scheme of the present invention: the usage ratio of the 5-bromo-1-pentanol, 1-methylpyrrolidine, anhydrous potassium carbonate and anhydrous acetonitrile in step a1 is 0.1 mol: 0.1 mol: 0.11-0.13 mol: 60-80 mL.

[0013] As a further solution of the present invention: the usage ratio of the cationic intermediate, triethylamine, anhydrous acetonitrile and methacryloyl chloride solution in step a2 is 10 mmol: 11-13 mmol: 30-35 mL: 10-12 mL.

[0014] As a further solution of the present invention: the methacryloyl chloride solution in step a2 is a solution formed by dissolving methacryloyl chloride in anhydrous acetonitrile at a ratio of 10 mmol:10 mL.

[0015] As a further solution of the present invention: the usage ratio of the vinyl ethylene carbonate, trifluoroethyl methacrylate, cationic monomer, azobisisobutyronitrile and deionized water in step a3 is 20-25g:1.2-2.8g:0.9-1.5g:0.02-0.04g:50-60mL.

[0016] As a further solution of the present invention: the dispersed modified carbon nanotubes are prepared by the following steps:

[0017] Step b1: Add multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir and react for 15-20 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then heat to 90-95°C and continue stirring and reacting for 4-5 hours. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 60-65°C for 3-5 hours to obtain oxidized modified carbon nanotubes;

[0018] Step b2: adding oxidized modified carbon nanotubes, ferric nitrate nonahydrate, cobalt dichloride hexahydrate, ammonia water and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introducing nitrogen protection, stirring the reaction for 15-20 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then heating to 80-85°C and continuing to stir the reaction for 4-5 hours, then heating to 180-185°C and continuing to stir the reaction for 4-5 hours, after the reaction is completed, cooling the reaction product to room temperature, then centrifuging, washing the precipitate with distilled water for 2-3 times, then placing it in a vacuum drying oven, drying it at a temperature of 80-85°C for 2-3 hours, then adding melamine and placing it in a tubular furnace, calcining it at a temperature of 850-900°C for 2-3 hours, then cooling it with the furnace to obtain nitrogen-doped loaded modified carbon nanotubes;

[0019] Step b3: Add nitrogen-doped loaded modified carbon nanotubes, γ-methacryloxypropyltrimethoxysilane, deionized water and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction for 10-15 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then raise the temperature to 80-85°C and continue stirring the reaction for 2-3 hours. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 60-65°C for 3-4 hours to obtain dispersed modified carbon nanotubes.

[0020] As a further solution of the present invention: the usage ratio of the multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step b1 is 2g:30-35mL:10-12mL.

[0021] As a further solution of the present invention: the mass fraction of the concentrated sulfuric acid in step b1 is 98%; the mass fraction of the concentrated nitric acid is 68%.

[0022] As a further solution of the present invention: the usage ratio of the oxidized modified carbon nanotubes, ferric nitrate nonahydrate, cobalt dichloride hexahydrate, ammonia water, anhydrous ethanol and melamine in step b2 is 2g: 0.2-0.25g: 0.08-0.16g: 5-9mL: 60-70mL: 0.1-0.5g.

[0023] As a further solution of the present invention: the mass fraction of the ammonia water in step b2 is 20-25%.

[0024] As a further solution of the present invention: the usage ratio of the nitrogen-doped loaded modified carbon nanotubes, γ-methacryloxypropyltrimethoxysilane, deionized water and anhydrous ethanol in step b3 is 2g:8-10mL:10-12mL:30-35mL.

[0025] As a further solution of the present invention: a method for preparing a composite sodium ion battery solid electrolyte comprises the following steps:

[0026] Step 1: Weigh 32-36 parts of high-performance polymer, 0.5-2.5 parts of dispersed modified carbon nanotubes, 8-10 parts of sodium perchlorate, 0.01-0.03 parts of azobisisobutyronitrile and 75-85 parts of anhydrous tetrahydrofuran according to weight parts, and set aside;

[0027] Step 2: Stir and mix the high-performance polymer, dispersed modified carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran evenly, then pour them into a PTFE mold, place them in a vacuum drying oven, dry them at a temperature of 80-85°C for 10-12h, and then cut them into shapes to obtain a composite sodium ion battery solid electrolyte.

[0028] Beneficial effects of the present invention:

[0029] The invention discloses a composite sodium ion battery solid electrolyte and a preparation method thereof. The composite sodium ion battery solid electrolyte is obtained by stirring and mixing a high-performance polymer, dispersed modified carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran evenly, and then drying and cutting into shape. The preparation method uses the high-performance polymer as a main raw material and adds the dispersed modified carbon nanotubes thereto, giving full play to the advantages of each component, effectively improving the ionic conductivity of the solid electrolyte, effectively improving the electrochemical performance of the sodium ion battery, and having excellent chemical stability, significantly improving the cycle stability and safety of the all-solid-state sodium ion battery, extending the service life, and avoiding the safety hazards of traditional liquid electrolytes such as volatility and explosion. Moreover, the preparation method is simple and feasible, easy to operate, low in cost, and conducive to large-scale commercial application.

[0030] In the process of preparing the composite sodium ion battery solid electrolyte, a high-performance polymer is first prepared. First, 5-bromo-1-pentanol and 1-methylpyrrolidine are reacted, and the bromine atom on the 5-bromo-1-pentanol reacts with the tertiary amine group on the 1-methylpyrrolidine to form a quaternary ammonium cationic group, and a hydroxyl group is introduced at the same time to obtain a cationic intermediate. Then, the cationic intermediate and methacryloyl chloride react, and the hydroxyl group on the cationic intermediate reacts with the acyl chloride group on the methacryloyl chloride to obtain a cationic monomer. Finally, vinyl ethylene carbonate, trifluoroethyl methacrylate, and the cationic monomer are used as polymerization monomers for polymerization to obtain a high-performance polymer. The high-performance polymer is obtained. The polymer molecular chain contains a large number of cationic groups, which can interact with sodium ions, promote the migration of sodium ions in the solid electrolyte, improve the ion conduction efficiency, and form channels that are conducive to the transmission of sodium ions, so that the electrochemical performance of the electrochemical performance can be improved. In addition, the high-performance polymer molecular chain contains a large number of CF bonds, which helps to improve the wettability between the solid electrolyte and the electrode, making the interface contact better, which is conducive to ion transmission and charge transfer. It can also improve the resistance of the solid electrolyte to chemical substances and prevent the solid electrolyte from being corroded or degraded. At the same time, the high temperature resistance is improved to ensure the long-term stability of the battery.

[0031] In the process of preparing the composite sodium ion battery solid electrolyte, a dispersed modified carbon nanotube is also prepared. First, the multi-walled carbon nanotube is treated with concentrated sulfuric acid and concentrated nitric acid to introduce a large number of active groups into the surface of the multi-walled carbon nanotube to obtain oxidized modified carbon nanotube. Then, iron nitrate nonahydrate and cobalt dichloride hexahydrate are used as raw materials to load iron-cobalt composite oxide on the surface and inner cavity of the oxidized modified carbon nanotube. Melamine is used as a nitrogen source. After calcination, nitrogen atoms are doped into the carbon nanotube to obtain nitrogen-doped loaded modified carbon nanotube. Finally, γ-methacryloxypropyltrimethoxysilane is used to modify the nitrogen-doped loaded modified carbon nanotube. γ-methacryloxypropyltrimethoxysilane can be grafted to the nitrogen-doped loaded modified carbon nanotube after hydrolysis. The surface of the carbon nanotubes is simultaneously introduced with alkenyl groups to obtain dispersed modified carbon nanotubes; the dispersed modified carbon nanotubes have excellent dispersibility after modification, so that they can be evenly distributed in the solid electrolyte, and after the alkenyl groups are introduced, they can be polymerized and grafted onto high-performance polymers, and the connection in the form of chemical bonds can improve their mechanical strength and stability, and the carbon nanotubes can further improve the electronic conduction ability of the solid electrolyte after loading iron-cobalt composite oxides, thereby improving the overall conductivity of the solid electrolyte, and after doping with nitrogen atoms, the active sites on the surface of the solid electrolyte can be increased, which can interact more effectively with sodium ions, promote the migration and transmission of sodium ions, reduce interface resistance, make the transmission of sodium ions at the interface smoother, and improve the charge and discharge efficiency of the battery. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] This embodiment is a method for preparing a composite sodium ion battery solid electrolyte, comprising the following steps:

[0035] Step S1: 0.1 mol 5-bromo-1-pentanol, 0.1 mol 1-methylpyrrolidine, 0.11 mol anhydrous potassium carbonate and 60 mL anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred at 0° C. and a stirring rate of 300 r / min for 1 h, and then the mixture is heated to 50° C. and the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at 50° C. for 3 h to obtain a cationic intermediate;

[0036] Step S2: 10 mmol of the cationic intermediate, 11 mmol of triethylamine and 30 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 0° C. and a stirring rate of 300 r / min for 20 min, and then 10 mL of methacryloyl chloride is added dropwise while stirring. The methacryloyl chloride solution formed by dissolving 10 mmol:10 mL of methacryloyl chloride in anhydrous acetonitrile is added dropwise, and the dropping rate is controlled to be 1 drop / s. After the addition is completed, the stirring reaction is continued for 20 min, and then the temperature is raised to 45° C. and the stirring reaction is continued for 4 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed twice with petroleum ether to obtain a cationic monomer;

[0037] Step S3: 20 g of vinyl ethylene carbonate, 1.2 g of trifluoroethyl methacrylate, 0.9 g of a cationic monomer, 0.02 g of azobisisobutyronitrile and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 20° C. and a stirring rate of 300 r / min for 1 h, and then the mixture was heated to 65° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at 50° C. for 5 h to obtain a high-performance polymer.

[0038] Step S4: 2 g of multi-walled carbon nanotubes, 30 mL of concentrated sulfuric acid with a mass fraction of 98%, and 10 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube, and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20° C. and a stirring rate of 300 r / min for 15 min, and then the temperature is raised to 90° C. and the stirring reaction is continued for 4 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain oxidized modified carbon nanotubes;

[0039] Step S5: 2g of oxidized modified carbon nanotubes, 0.2g of ferric nitrate nonahydrate, 0.08g of cobalt dichloride hexahydrate, 5mL of 20% ammonia water and 60mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 20°C and a stirring rate of 300r / min for 15min, and then the mixture is heated to 80°C and stirred for reaction for 4h, and then the mixture is heated to 180°C and stirred for reaction for 4h. After the reaction, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed with distilled water twice, and then placed in a vacuum drying oven and dried at a temperature of 80°C for 2h. Then 0.1g of melamine is added and placed in a tubular furnace, and calcined at a temperature of 850°C for 2h, and then cooled with the furnace to obtain nitrogen-doped loaded modified carbon nanotubes;

[0040] Step S6: 2 g of nitrogen-doped loaded modified carbon nanotubes, 8 mL of γ-methacryloxypropyltrimethoxysilane, 10 mL of deionized water and 30 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for 10 min at a temperature of 25° C. and a stirring rate of 300 r / min, and then the mixture was heated to 80° C. and stirred for 2 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain dispersed modified carbon nanotubes.

[0041] Step S7: 32 parts of high-performance polymer, 0.5 parts of dispersed modified carbon nanotubes, 8 parts of sodium perchlorate, 0.01 parts of azobisisobutyronitrile and 75 parts of anhydrous tetrahydrofuran were weighed in parts by weight for later use;

[0042] Step S8: The high-performance polymer, dispersed modified carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran are stirred and mixed evenly, then poured into a PTFE mold, and then placed in a vacuum drying oven, dried at a temperature of 80° C. for 10 hours, and then cut into shapes to obtain a composite sodium ion battery solid electrolyte.

[0043] Embodiment 2:

[0044] This embodiment is a method for preparing a composite sodium ion battery solid electrolyte, comprising the following steps:

[0045] Step S1: 0.1 mol 5-bromo-1-pentanol, 0.1 mol 1-methylpyrrolidine, 0.12 mol anhydrous potassium carbonate and 70 mL anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The reaction is stirred for 1.5 hours at a temperature of 3° C. and a stirring rate of 350 r / min, and then the temperature is raised to 52° C. and the stirring reaction is continued for 9 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, the filtrate is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at a temperature of 52° C. for 4 hours to obtain a cationic intermediate;

[0046] Step S2: 10 mmol of the cationic intermediate, 12 mmol of triethylamine and 32 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 25 min at a temperature of 3° C. and a stirring rate of 350 r / min. Then, 11 mL of methacryloyl chloride is added dropwise while stirring. The methacryloyl chloride solution formed by dissolving 10 mmol:10 mL of methacryloyl chloride in anhydrous acetonitrile is added dropwise. The dropping rate is controlled to be 1 drop / s. After the addition is completed, the reaction is continued to stir for 25 min, and then the temperature is raised to 48° C. and the reaction is continued to stir for 4.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed twice with petroleum ether to obtain a cationic monomer;

[0047] Step S3: 22 g of vinyl ethylene carbonate, 2 g of trifluoroethyl methacrylate, 1.2 g of cationic monomer, 0.03 g of azobisisobutyronitrile and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred at 22° C. and a stirring rate of 350 r / min for 1.5 h, and then the mixture was heated to 70° C. and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at 52° C. for 5.5 h to obtain a high-performance polymer.

[0048] Step S4: 2 g of multi-walled carbon nanotubes, 32 mL of concentrated sulfuric acid with a mass fraction of 98%, and 11 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube, and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 22° C. and a stirring rate of 350 r / min for 18 min, and then the mixture is heated to 92° C. and stirred for reaction for 4.5 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 4 h to obtain oxidized modified carbon nanotubes;

[0049] Step S5: 2g of oxidized modified carbon nanotubes, 0.22g of ferric nitrate nonahydrate, 0.12g of cobalt dichloride hexahydrate, 7mL of 22% ammonia water and 65mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted for 18min at a temperature of 22°C and a stirring rate of 350r / min, and then the mixture is heated to 82°C and stirred for 4.5h, and then the mixture is heated to 182°C and stirred for 4.5h. After the reaction is completed, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 82°C for 2.5h. Then, 0.3g of melamine is added and placed in a tubular furnace, and calcined at a temperature of 870°C for 2.5h, and then cooled with the furnace to obtain nitrogen-doped loaded modified carbon nanotubes;

[0050] Step S6: 2 g of nitrogen-doped loaded modified carbon nanotubes, 9 mL of γ-methacryloxypropyltrimethoxysilane, 11 mL of deionized water and 32 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 12 min, and then the mixture was heated to 82° C. and stirred for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at 62° C. for 3.5 h to obtain dispersed modified carbon nanotubes.

[0051] Step S7: 34 parts of high-performance polymer, 1.5 parts of dispersed modified carbon nanotubes, 9 parts of sodium perchlorate, 0.02 parts of azobisisobutyronitrile and 80 parts of anhydrous tetrahydrofuran were weighed in parts by weight for later use;

[0052] Step S8: The high-performance polymer, dispersed modified carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran are stirred and mixed evenly, then poured into a PTFE mold, and then placed in a vacuum drying oven, dried at a temperature of 82° C. for 11 hours, and then cut into shapes to obtain a composite sodium ion battery solid electrolyte.

[0053] Embodiment 3:

[0054] This embodiment is a method for preparing a composite sodium ion battery solid electrolyte, comprising the following steps:

[0055] Step S1: 0.1 mol 5-bromo-1-pentanol, 0.1 mol 1-methylpyrrolidine, 0.13 mol anhydrous potassium carbonate and 80 mL anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 5° C. and a stirring rate of 400 r / min for 2 h, and then the mixture is heated to 55° C. and stirred for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain a cationic intermediate;

[0056] Step S2: 10 mmol of the cationic intermediate, 13 mmol of triethylamine and 35 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 30 min, and then 12 mL of methacryloyl chloride is added dropwise while stirring. The methacryloyl chloride solution formed by dissolving 10 mmol:10 mL of methacryloyl chloride in anhydrous acetonitrile is added dropwise, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 30 min, and then the temperature is raised to 50° C. and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed with petroleum ether 3 times to obtain a cationic monomer;

[0057] Step S3: 25 g of vinyl ethylene carbonate, 2.8 g of trifluoroethyl methacrylate, 1.5 g of a cationic monomer, 0.04 g of azobisisobutyronitrile and 60 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred and reacted at a temperature of 25° C. and a stirring rate of 400 r / min for 2 h, and then the mixture was heated to 75° C. and continued to stir and react for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at a temperature of 55° C. for 6 h to obtain a high-performance polymer;

[0058] Step S4: 2 g of multi-walled carbon nanotubes, 35 mL of concentrated sulfuric acid with a mass fraction of 98%, and 12 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube, and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 400 r / min for 20 min, and then the temperature is raised to 95° C. and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 5 h to obtain oxidized modified carbon nanotubes;

[0059] Step S5: 2g of oxidized modified carbon nanotubes, 0.25g of ferric nitrate nonahydrate, 0.16g of cobalt dichloride hexahydrate, 9mL of 25% ammonia water and 70mL of anhydrous ethanol are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted for 20min at a temperature of 25°C and a stirring rate of 400r / min, and then the mixture is heated to 85°C and stirred for 5h, and then the mixture is heated to 185°C and stirred for 5h. After the reaction, the reaction product is cooled to room temperature, and then centrifuged. The precipitate is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 3h. Then, 0.5g of melamine is added and placed in a tubular furnace, and calcined at a temperature of 900°C for 3h, and then cooled with the furnace to obtain nitrogen-doped loaded modified carbon nanotubes;

[0060] Step S6: 2 g of nitrogen-doped loaded modified carbon nanotubes, 10 mL of γ-methacryloxypropyltrimethoxysilane, 12 mL of deionized water and 35 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 15 min, and then the mixture was heated to 85° C. and stirred for 3 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was placed in a vacuum drying oven and dried at a temperature of 65° C. for 4 h to obtain dispersed modified carbon nanotubes.

[0061] Step S7: 36 parts of high-performance polymer, 2.5 parts of dispersed modified carbon nanotubes, 10 parts of sodium perchlorate, 0.03 parts of azobisisobutyronitrile and 85 parts of anhydrous tetrahydrofuran were weighed in parts by weight for later use;

[0062] Step S8: The high-performance polymer, dispersed modified carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran are stirred and mixed evenly, then poured into a PTFE mold, and then placed in a vacuum drying oven, dried at a temperature of 85° C. for 12 hours, and then cut into shapes to obtain a composite sodium ion battery solid electrolyte.

[0063] Comparative Example 1:

[0064] This comparative example is a method for preparing a composite sodium ion battery solid electrolyte, comprising the following steps:

[0065] Step S1: Weigh 36 parts of polyethylene oxide, 10 parts of sodium perchlorate, 0.03 parts of azobisisobutyronitrile and 85 parts of anhydrous tetrahydrofuran according to weight and set aside;

[0066] Step S2: Stir and mix polyethylene oxide, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran evenly, then pour them into a PTFE mold, place them in a vacuum drying oven, dry them at 85°C for 12 hours, and then cut them into shapes to obtain a composite sodium ion battery solid electrolyte.

[0067] Comparative Example 2:

[0068] This comparative example is a method for preparing a composite sodium ion battery solid electrolyte, comprising the following steps:

[0069] Step S1: 0.1 mol 5-bromo-1-pentanol, 0.1 mol 1-methylpyrrolidine, 0.13 mol anhydrous potassium carbonate and 80 mL anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 5° C. and a stirring rate of 400 r / min for 2 h, and then the mixture is heated to 55° C. and stirred for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain a cationic intermediate;

[0070] Step S2: 10 mmol of the cationic intermediate, 13 mmol of triethylamine and 35 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 30 min, and then 12 mL of methacryloyl chloride is added dropwise while stirring. The methacryloyl chloride solution formed by dissolving 10 mmol:10 mL of methacryloyl chloride in anhydrous acetonitrile is added dropwise, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 30 min, and then the temperature is raised to 50° C. and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed with petroleum ether 3 times to obtain a cationic monomer;

[0071] Step S3: 25 g of vinyl ethylene carbonate, 2.8 g of trifluoroethyl methacrylate, 1.5 g of a cationic monomer, 0.04 g of azobisisobutyronitrile and 60 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred and reacted at a temperature of 25° C. and a stirring rate of 400 r / min for 2 h, and then the mixture was heated to 75° C. and continued to stir and react for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at a temperature of 55° C. for 6 h to obtain a high-performance polymer;

[0072] Step S4: 36 parts of a high-performance polymer, 10 parts of sodium perchlorate, 0.03 parts of azobisisobutyronitrile and 85 parts of anhydrous tetrahydrofuran were weighed in parts by weight for later use;

[0073] Step S5: The high-performance polymer, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran are stirred and mixed evenly, then poured into a PTFE mold, and then placed in a vacuum drying oven, dried at a temperature of 85° C. for 12 hours, and then cut into shapes to obtain a composite sodium ion battery solid electrolyte.

[0074] Comparative Example 3:

[0075] This comparative example is a method for preparing a composite sodium ion battery solid electrolyte, comprising the following steps:

[0076] Step S1: 0.1 mol 5-bromo-1-pentanol, 0.1 mol 1-methylpyrrolidine, 0.13 mol anhydrous potassium carbonate and 80 mL anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 5° C. and a stirring rate of 400 r / min for 2 h, and then the mixture is heated to 55° C. and stirred for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filtrate is rotary evaporated to remove the solvent, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain a cationic intermediate;

[0077] Step S2: 10 mmol of the cationic intermediate, 13 mmol of triethylamine and 35 mL of anhydrous acetonitrile are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 5° C. and a stirring rate of 400 r / min for 30 min, and then 12 mL of methacryloyl chloride is added dropwise while stirring. The methacryloyl chloride solution formed by dissolving 10 mmol:10 mL of methacryloyl chloride in anhydrous acetonitrile is added dropwise, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the stirring reaction is continued for 30 min, and then the temperature is raised to 50° C. and the stirring reaction is continued for 5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then washed with petroleum ether 3 times to obtain a cationic monomer;

[0078] Step S3: 25 g of vinyl ethylene carbonate, 2.8 g of trifluoroethyl methacrylate, 1.5 g of a cationic monomer, 0.04 g of azobisisobutyronitrile and 60 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred and reacted at a temperature of 25° C. and a stirring rate of 400 r / min for 2 h, and then the mixture was heated to 75° C. and continued to stir and react for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. The mixture was then placed in a vacuum drying oven and dried at a temperature of 55° C. for 6 h to obtain a high-performance polymer;

[0079] Step S4: 36 parts of a high-performance polymer, 2.5 parts of multi-walled carbon nanotubes, 10 parts of sodium perchlorate, 0.03 parts of azobisisobutyronitrile and 85 parts of anhydrous tetrahydrofuran were weighed in parts by weight and set aside;

[0080] Step S5: The high-performance polymer, multi-walled carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran are stirred and mixed evenly, then poured into a PTFE mold, and then placed in a vacuum drying oven, dried at a temperature of 85° C. for 12 hours, and then cut into shapes to obtain a composite sodium ion battery solid electrolyte.

[0081] Performance Testing:

[0082] A: Ionic conductivity test;

[0083] The 25° C. ionic conductivity of the composite sodium ion battery solid electrolyte in Examples 1-3 and Comparative Examples 1-3 was tested;

[0084] B: Initial discharge specific capacity and capacity retention rate test;

[0085] The positive electrode sheet is made of sodium iron phosphate, PVDF and acetylene black in a mass ratio of 8:1:1, which are ground and added to DMF to form a slurry, which is evenly scraped onto aluminum foil, dried and cut;

[0086] The negative electrode is a sodium plate;

[0087] The solid electrolyte is the composite sodium ion battery solid electrolyte in Examples 1-3 and Comparative Examples 1-3;

[0088] The positive electrode sheet, the negative electrode sheet and the composite sodium ion battery solid electrolyte are assembled to form an all-solid-state sodium ion battery, and the all-solid-state sodium ion battery is tested for initial discharge specific capacity at a rate of 0.2C at 55°C, and its capacity retention rate is tested after 100 stable cycles;

[0089] The test results are shown in the following table:

[0090] sample Ionic conductivity, S / cm Initial discharge specific capacity, mAh / g Capacity retention rate, % Example 1 <![CDATA[4.82×10 -4 ]]> 168.3 89.8 Example 2 <![CDATA[5.36×10 -4 ]]> 174.1 92.5 Example 3 <![CDATA[5.75×10 -4 ]]> 181.4 95.1 Comparative Example 1 <![CDATA[7.69×10 -6 ]]> 117.3 71.3 Comparative Example 2 <![CDATA[9.21×10 -5 ]]> 143.5 89.3 Comparative Example 3 <![CDATA[2.96×10 -4 ]]> 159.2 84.6

[0091] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the use of high-performance polymers and the addition of dispersed modified carbon nanotubes can effectively improve the electrochemical performance and cycle stability of all-solid-state sodium ion batteries.

[0092] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0093] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A composite sodium ion battery solid electrolyte, characterized in that: It comprises the following components in parts by weight: 32-36 parts of high-performance polymer, 0.5-2.5 parts of dispersed modified carbon nanotubes, 8-10 parts of sodium perchlorate, 0.01-0.03 parts of azobisisobutyronitrile and 75-85 parts of anhydrous tetrahydrofuran; Wherein, the high performance polymer is prepared by the following steps: Step a1: 5-bromo-1-pentanol, 1-methylpyrrolidine, anhydrous potassium carbonate and anhydrous acetonitrile are stirred for reaction. After the reaction is completed, the reaction product is cooled, then vacuum filtered, the filtrate is rotary evaporated, and then dried to obtain a cationic intermediate; Step a2: Stirring the cationic intermediate, triethylamine and anhydrous acetonitrile for reaction, then adding methacryloyl chloride solution dropwise while stirring, and continuing to stir the reaction after the addition is complete. After the reaction is complete, the reaction product is cooled and then rotary evaporated to obtain a cationic monomer; Step a3: stirring and reacting vinyl ethylene carbonate, trifluoroethyl methacrylate, cationic monomer, azobisisobutyronitrile and deionized water. After the reaction, cooling the reaction product, then rotary evaporating, and then drying to obtain a high-performance polymer.

2. A composite sodium ion battery solid electrolyte according to claim 1, characterized in that: The usage ratio of the 5-bromo-1-pentanol, 1-methylpyrrolidine, anhydrous potassium carbonate and anhydrous acetonitrile in step a1 is 0.1 mol: 0.1 mol: 0.11-0.13 mol: 60-80 mL.

3. A composite sodium ion battery solid electrolyte according to claim 1, characterized in that: The cationic intermediate, triethylamine, anhydrous acetonitrile and methacryloyl chloride solution in step a2 are used in a ratio of 10 mmol: 11-13 mmol: 30-35 mL: 10-12 mL; the methacryloyl chloride solution is a solution formed by dissolving methacryloyl chloride in anhydrous acetonitrile at a ratio of 10 mmol: 10 mL.

4. A composite sodium ion battery solid electrolyte according to claim 1, characterized in that: The usage ratio of the vinyl ethylene carbonate, trifluoroethyl methacrylate, cationic monomer, azobisisobutyronitrile and deionized water in step a3 is 20-25 g: 1.2-2.8 g: 0.9-1.5 g: 0.02-0.04 g: 50-60 mL.

5. A composite sodium ion battery solid electrolyte according to claim 1, characterized in that: The dispersed modified carbon nanotubes are prepared by the following steps: Step b1: stirring and reacting multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid, cooling the reaction product after the reaction is completed, centrifuging it, washing and drying the precipitate, and obtaining oxidized modified carbon nanotubes; Step b2: stirring and reacting the oxidized modified carbon nanotubes, ferric nitrate nonahydrate, cobalt dichloride hexahydrate, ammonia water and anhydrous ethanol, cooling the reaction product after the reaction, centrifuging it, washing and drying the precipitate, adding melamine and calcining it to obtain nitrogen-doped loaded modified carbon nanotubes; Step b3: stirring the nitrogen-doped loaded modified carbon nanotubes, γ-methacryloxypropyltrimethoxysilane, deionized water and anhydrous ethanol to react, cooling the reaction product after the reaction is completed, then centrifuging, and drying the precipitate to obtain dispersed modified carbon nanotubes.

6. A composite sodium ion battery solid electrolyte according to claim 5, characterized in that: The usage ratio of the multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step b1 is 2g:30-35mL:10-12mL; the mass fraction of the concentrated sulfuric acid is 98%; the mass fraction of the concentrated nitric acid is 68%.

7. A composite sodium ion battery solid electrolyte according to claim 5, characterized in that: The dosage ratio of the oxidized modified carbon nanotubes, ferric nitrate nonahydrate, cobalt dichloride hexahydrate, ammonia water, anhydrous ethanol and melamine in step b2 is 2g: 0.2-0.25g: 0.08-0.16g: 5-9mL: 60-70mL: 0.1-0.5g; the mass fraction of the ammonia water is 20-25%.

8. A composite sodium ion battery solid electrolyte according to claim 5, characterized in that: The amount ratio of the nitrogen-doped loaded modified carbon nanotubes, γ-methacryloxypropyltrimethoxysilane, deionized water and anhydrous ethanol in step b3 is 2g: 8-10mL: 10-12mL: 30-35mL.

9. A method for preparing a composite sodium ion battery solid electrolyte according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Weigh 32-36 parts of high-performance polymer, 0.5-2.5 parts of dispersed modified carbon nanotubes, 8-10 parts of sodium perchlorate, 0.01-0.03 parts of azobisisobutyronitrile and 75-85 parts of anhydrous tetrahydrofuran according to weight parts, and set aside; Step 2: Stir and mix the high-performance polymer, dispersed modified carbon nanotubes, sodium perchlorate, azobisisobutyronitrile and anhydrous tetrahydrofuran evenly, then pour them into a PTFE mold, place them in a vacuum drying oven, dry them at a temperature of 80-85°C for 10-12h, and then cut them into shapes to obtain a composite sodium ion battery solid electrolyte.